2015
DOI: 10.1111/1541-4337.12161
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modification of Polysaccharides and Resulting Bioactivities

Abstract: Polysaccharides are ideal natural resources for supplements and pharmaceuticals that have received more and more attention over the years. Natural polysaccharides have been shown to have fewer side effects, but because of their inherently physicochemical properties, their bioactivities were difficult to compare with those of synthetic drugs. Thus, researchers have modified the structures and properties of natural polysaccharides based on structure-activity relationships and have obtained better functionally im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
191
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 414 publications
(200 citation statements)
references
References 108 publications
2
191
0
7
Order By: Relevance
“…A comparison of the current study findings with the aforementioned showed that APS extracted under dual‐frequency ultrasound had a greater potential to lower the proliferation of ˙OH radicals, and could greatly reduce oxidative impairments. This result is supported by Li et al () who have reported that ultrasonic disruption intensifies the degradation of high molecular weight polysaccharides to low molecular weight polysaccharides since low molecular weight polysaccharides possess a more reductive hydroxyl group to accept and eradicate free radicals (Leung, Zhao, Ho, & Wu, ). IC 50 value were reported as 0.42, 0.38, 0.43, and 0.56 mg/ml for APS 10 , APS 20 , APS 30 , and APS control , respectively.…”
Section: Resultssupporting
confidence: 56%
“…A comparison of the current study findings with the aforementioned showed that APS extracted under dual‐frequency ultrasound had a greater potential to lower the proliferation of ˙OH radicals, and could greatly reduce oxidative impairments. This result is supported by Li et al () who have reported that ultrasonic disruption intensifies the degradation of high molecular weight polysaccharides to low molecular weight polysaccharides since low molecular weight polysaccharides possess a more reductive hydroxyl group to accept and eradicate free radicals (Leung, Zhao, Ho, & Wu, ). IC 50 value were reported as 0.42, 0.38, 0.43, and 0.56 mg/ml for APS 10 , APS 20 , APS 30 , and APS control , respectively.…”
Section: Resultssupporting
confidence: 56%
“…As shown in the figure, elution volume of graft copolymers shifted to higher values compared to that of alginate, which resulted in a significant decrease in the molecular weights as presented in Table . This result demonstrates that microwave irradiation used in the grafting reaction may cause cleavage of some bonds in the alginate chains . However, when grafting percentages increased from 58% to 88%, all types of average molecular weights increased proportionally, due to the formation of much longer PDEAAm chains in the copolymer structure.…”
Section: Resultsmentioning
confidence: 90%
“…Ultrasonic degradation of polysaccharides was shown to enhance hydroxyl and superoxide anion radical scavenging capacity, chelating iron ion ability and reducing power (Zhou et al 2008); this phenomenon could be attributed to the fact that a decreasing of Mw and viscosity of HA may influence its bioactivities. In addition, the long main chain and high viscosity of polysaccharides decrease the absorption and diffusion properties, thus limiting their biological activity (Li et al 2016). Therefore, an effective method to resolve this problem is by degrading the main chain (Zhou et al 2008).…”
Section: Dpph and No Scavenging Activitymentioning
confidence: 99%